Pelatihan Dasar-Dasar Komputer dan Teknologi Informasi bagi Siswa Sekolah Dasar di Desa Masbagik Timur - Qusyairi, Muhammad; Mu'ammaruddin; M. Abdul Azmi; Samsul Hadi; Susilawati indah cahayani; M.taufik walhidayah (Jurnal Teknologi Informasi untuk Masyarakat, 2024)
The development of information technology demands society to participate in developing itself. But the fact is that there are still many people who do not understand technology especially related to computers. More specifically in primary school students, there is still minimal knowledge about computer operation and Microsoft word. Therefore it is necessary to conduct training on the basics of computers. This training will be held on October 1-3, 2024 at the hall of the village office Masbagik Timur. This training activity consists of 4 stages, namely the analysis of needs and identification of problems of students in the village of East Masbagik related to computer technology, the preparation of training materials, this activity is training for 3 days, and the last is the evaluation of training activities. Based on the training activities it was concluded that these training activities went smoothly and followed the initial objectives of the training activities. The enthusiasm of primary school students to attend this training is quite high